Survey on Android application for power efficiency in private cloud (International Journal of Engineering and Computer Science, 2017)
Nowadays distributed systems are used everywhere. In distributed environment as there are numbers of processes running in the environment from which some processes are not required to execute for that specific instance. To schedule that process and balance the energy load in network traffic. We use the OFF concept. In these OFF concept, we close the unwanted process running in the background using the Ad-hoc network. In private cloud it is not possible to administrate all machines at the same instance of time, to overcome this problem propose system gives the notification message to the administrator when particular machine having greater load value. This system also provides the remote operation of processes using an android device. The Administrator can remotely shut down the systems as well as stop the unwanted processes. Also, this provides the single URL for the same task in the absence of android device. An evaluation and comparative study of the proposed approach provides evidence of its merits in terms of elasticity, energy efficiency, and scalability, as well as of its feasibility in the presence of high workload rate.